2006
DOI: 10.1002/bdra.20293
|View full text |Cite
|
Sign up to set email alerts
|

Problems in using birth certificate files in the capture‐recapture model to estimate the completeness of case ascertainment in a population‐based birth defects registry in New York State

Abstract: Discrepancies in birth defect categories in the two data sources and false positives in the birth certificates were the major problems encountered in estimating the completeness of the CMR using the simple two-source capture-recapture method. The estimated completeness for selected major birth defects was only about 71%. Stratified analyses resulted in relatively high estimated completeness for oral clefts (90%) and Down syndrome (88%). CONCLUSIONS Although the birth certificate data was not a good source for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…First, documentation of birth defects on birth certificates can be inconsistent, with variable sensitivities reported in existing literature. 37,38 However, the abdominal wall defect rate in this study is comparable to recent national estimates, 18,20,34 suggesting our data provide a reasonable representation of abdominal wall defect rates. Second, the vast majority of states used the 1989 version of the birth certificate in which omphalocele and gastroschisis were identified by the same code, making separation of the two conditions impossible.…”
Section: Discussionsupporting
confidence: 85%
“…First, documentation of birth defects on birth certificates can be inconsistent, with variable sensitivities reported in existing literature. 37,38 However, the abdominal wall defect rate in this study is comparable to recent national estimates, 18,20,34 suggesting our data provide a reasonable representation of abdominal wall defect rates. Second, the vast majority of states used the 1989 version of the birth certificate in which omphalocele and gastroschisis were identified by the same code, making separation of the two conditions impossible.…”
Section: Discussionsupporting
confidence: 85%
“…Similar results were observed in other studies 15,16,17 . Wang et al 20 observed reporting of 88.7% in multiple cases and 69.5% in cases with single defects. Olsen et al 18 however, analyzing the cases registered in the Birth Certificate, showed that these had a higher chance of having a single and minor anomaly, which was not verified in the CMR.…”
Section: Discussionmentioning
confidence: 95%
“…The underreporting for major birth defects, in studies performed in the USA with the Birth Certificate, which is similar to the Brazilian, varied from 55% to 88% 14,15,16,17,18,19,20,21 . In our study, even if it was a high percentage it was better than in the USA, although similar to a study made in Birmingham, England, where underreporting was 32% 22 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…By relying on birth certificate data, some children with Down syndrome were not identified, because recording of this at birth is known to be incomplete 38. As Down syndrome predisposes mainly to leukemia, however, residual confounding would not have affected other cancer types 39.…”
Section: Discussionmentioning
confidence: 99%